1978
DOI: 10.1136/bmj.1.6122.1239
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of insulin in diabetic patients: a dose-related effect on glucose production and utilisation

Abstract: 1239hydrate diet, reduced physical activity, and obesity may be the important factors implicated. And all these factors seem to operate in the Nauruan population.8This work was supported in part by a grant from the National Health and Medical Research Council of Australia. We thank the government of the Republic of Nauru for allowing the study to proceed, and Miss Roma Swan for typing the manuscript. ReferencesIPrior, I A M, et al, Lancet, 1966, 1, 333. 2 West, K M, Diabetes, 1974, 23, 841. 3 Zimmet, P, et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0
2

Year Published

1981
1981
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 15 publications
7
28
0
2
Order By: Relevance
“…Compensating mechanisms to combat hypoglycaemia later modified this pattern. Similar results have been reported by Issekutz et al [21] in diabetic dogs and more recently by Brown et al [22] in diabetic human subjects. These workers found that low insulin infusion rates affected only hepatic glucose production whereas at higher infusion rates both production and utilisation were affected.…”
Section: Discussionsupporting
confidence: 81%
“…Compensating mechanisms to combat hypoglycaemia later modified this pattern. Similar results have been reported by Issekutz et al [21] in diabetic dogs and more recently by Brown et al [22] in diabetic human subjects. These workers found that low insulin infusion rates affected only hepatic glucose production whereas at higher infusion rates both production and utilisation were affected.…”
Section: Discussionsupporting
confidence: 81%
“…Insulin has been shown to control NEFA concentration primarily by modulating output from peripheral stores [14]. On the other hand, the hepatic effect of insulin on glucose production is the predominant determinant of peripheral glucose concentration at low insulin concentrations, with a further effect in increased peripheral uptake only at high physiological levels [15,16]. A bolus of insulin alone (173 or 700 pmol/kg) caused an immediate rapid fall in plasma NEFA and glucose.…”
Section: Discussionmentioning
confidence: 99%
“…In fact this is NOT the case and is another error arising from extrapolating from in vitro rat data. It has been shown quite unequivocally that insulin at concentrations that are within the normal physiological range lowers blood glucose through inhibiting hepatic glucose production (Ra) without stimulating peripheral glucose uptake (Brown et al 1978). As hepatic glucose output is 'switched off' by the chalonic action of insulin, glucose concentration falls and glucose uptake actually decreases.…”
Section: Autacoids -Excitatory Substances Chalones -Inhibitory Substamentioning
confidence: 99%